Development of Loop-Mediated Isothermal Amplification Assay for Detection of Clinically Significant Members of Acinetobacter calcoaceticus–baumannii Complex and Associated Carbapenem Resistance - Sharma, Amit; Gaind, Rajni (Frontiers in Molecular Biosciences, 2021)
Background: Acinetobacter calcoaceticus-baumannii (ACB) complex has emerged as an important nosocomial pathogen, associated with life threatening infections, especially among ICU patients including neonates. Carbapenem resistance among Acinetobacter baumannii has emerged globally and is commonly mediated by blaOXA-23. Clinically significant infections with carbapenem resistant Acinetobacter baumannii (CRAB) are a major concern as therapeutic options are limited and high associated mortality. Early diagnosis of both pathogen and resistance is important to initiate the optimal therapy and prevent selection of resistance. In the current study, loop mediated isothermal amplification (LAMP) assay was developed for rapid detection of ACB complex and carbapenem resistance mediated by blaOXA-23. Methodology: Universal LAMP primers were designed for detection of significant members of ACB complex and carbapenem resistance targeting ITS 16S-23S rRNA gene and blaOXA-23 respectively. The optimal conditions for LAMP assay were standardized for each primer set using standard ATCC strains. The sensitivity of LAMP assay was assessed based on limit of detection (LOD) using different DNA concentration and colony count. The specificity of LAMP was determined using non-ACB complex and non-Acinetobacter species. The results of LAMP assay were compared with polymerase chain reaction (PCR). Results: The optimal temperature for LAMP assay was 65°C, and the detection time varied with various primers designed. Using ITS Ab1 primer, LOD of LAMP and PCR assays were 100pg/µl and 1ng/µl of DNA concentration and 104cfu/ml and 108cfu/ml of colony count respectively. LAMP assay was 10 and 104-fold more sensitive than PCR using DNA concentration and colony count respectively. The LAMP assay was found to be specific for clinically important ACB complex species. Significance of the study: LAMP assay can be applied for early detection of significant species of ACB complex from clinical samples and their carbapenem resistant variants. Depending on the emerging pathogen and locally prevalent resistance genes, LAMP assay can be modified for detection of colonization or infection by various resistant bugs.